Aripiprazole salts: II. Aripiprazole perchlorate - Freire Espeleta, Eleonora (2012)
The molecular structure of aripiprazole perchlorate (systematic name: 4-(2,3-dichlorophenyl)-1-{4-[(2-oxo-1,2,3,4-tetrahydroquinolin-7-yl)oxy]butyl} piperazin-1-ium perchlorate), C23H28Cl2N 3O2 +-ClO4-, does not differ substantially from the recently published structure of aripiprazole nitrate [Freire, Polla & Baggio (2012). Acta Cryst. C68, o170-o173]. Both compounds have almost identical bond distances, bond angles and torsion angles. The two different counter-ions occupy equivalent places in the two structures, giving rise to very similar first-order 'packing motifs'. However, these elemental arrangements interact with each other in different ways in the two structures, leading to two-dimensional arrays with quite different organizations.